How knowledge workers use the web - Sellen, Abigail; Murphy, Rachel; Shaw, Kate L. (Web Behavour Patterns, 2002)
We report on a diary study of how and why knowledge workers use the World Wide Web. By examining in detail a complete two-day set of Web activities from each of 24 people, we construct a framework with which to describe the different tasks knowledge workers undertake. By looking at the characteristics of each type of activity, we can see how certain activities are unsuited to particular kinds of technologies (e.g., mobile devices); how Web tools might be incrementally improved; and how we might better support knowledge workers’ Web tasks in the future.
CHI 2002, April 20-25, 2002, Minneapolis, Minnesota, USA